“Consciousness in Its Own Self Provides Its Own Standard”. Hegel and the Spirit as a Process of Thinking - Waibel, Violetta L. (ETHICS IN PROGRESS, 2022)
Hegel’s Phenomenology of Spirit develops not only the idea of absolute knowledge but also the notion of an inner criterion [Maßstab] of the spirit. The inner criterion or norm of knowledge is what, in the end of the speculative process, appears as the form of absolute knowledge. Experience and inner criterion are responsible for the development of the consciousness that has to become itself. Becoming and absolute, temporality and timelessness are the substance that becomes and is subject. The actuality of this method of analysis of spirit will be shown and discussed in this essay.